The theoretical adhesion of Staphylococcus aureus and Pseudomonas aeruginosa as nosocomial pathogens on 3D printing filament materials - Raouan, Safae Er; Zouine, Nouhaila; Harchli, Elhassan El; El Abed, Soumya; Sadiki, Moulay; Ghachtouli, Naima El; Lachkar, Mohammed; Ibnsouda, Saad Koraichi (Folia microbiologica, 2023)
Microbial infections and nosocomial diseases associated with biomaterial have become a major problem of public health and largely lead to revision surgery, which is painful and quite expensive for patients. These infections are caused by formation of biofilm, which present a difficulty of treatment with conventional antibiotics. The aim of our study is to investigate the theoretical adhesion of Staphylococcus aureus and Pseudomonas aeruginosa on four 3-dimensional printing filament materials used in the manufacture of medical equipment. Thus, the physicochemical properties of these microorganisms and all filament materials were determined using the contact angle measurements. Our results indicated that bacterial surfaces were hydrophilic, strongly electron donating and weakly electron accepting. In contrast, nylon, acrylonitrile butadiene-styrene, polyethylene terephthalate, and polylactic acid surfaces were hydrophobic and more electron-donor than electron-acceptor. In addition, according to the values of total free interaction energy ΔGTotal, Staphylococcus aureus was found unable to adhere to the filament materials except polyethylene terephthalate surface. However, Pseudomonas aeruginosa showed adhesion capacity only for acrylonitrile butadiene-styrene and polyethylene terephthalate surfaces. These findings imply that the usage of these 3D printed materials in the medical area necessitates more research into enhancing their resistance to bacterial adherence.
Keywords: styreny; butadieny; stafylokokové infekce; Butadienes; Polyethylene Terephthalates; infekce spojené se zdravotní péčí; Staphylococcus aureus; Acrylonitrile; polyethylentereftaláty; Bacterial Adhesion; akrylonitril; lidé; Pseudomonas aeruginosa; Cross Infection; Biofilms; Humans; Staphylococcal Infections; Styrenes; biofilmy; bakteriální adheze